President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2016)
ORNAC is dedicated to the promotion and advancement of excellence in the provision of safe perioperative care for patients. As perioperative nurses we need to ensure our practice is performed at a high standard and that patients benefit from our safe effective care.